White matter micro-structural changes in ART-naive and ART-treated children and adolescents infected with HIV in South Africa. (10th September 2015) - Hoare, Jacqueline; Fouche, Jean-Paul; Phillips, Nicole; Joska, John A.; Paul, Robert; Donald, Kirsten A.; Thomas, Kevin G.F.; Stein, Dan J.
<x xml:space="preserve">Abstract</x> Objective: To describe the effect of HIV on white matter integrity and neurocognitive function in children vertically infected with HIV, compared to a HIV-negative healthy control group. Design: Cross-sectional. Methods: We compared 75 HIV-infected children aged 6–16 years, including children on antiretroviral therapy (ART) and those who were ART-naive, with 30 controls on diffusion tensor imaging and a neuropsychological battery sensitive to fronto-striatal pathology. In a secondary analysis, we compared 'slow progressor' ART-naive children, children on ART without a diagnosis of encephalopathy and children on ART with HIV encephalopathy. Results: Compared to controls (n = 30), HIV-infected children (n = 75) displayed decreased fractional anisotropy and axial diffusion, and increased mean diffusivity and radial diffusion, indicating damaged neuronal microstructure. HIV-infected children performed poorly on the neuropsychological battery (P = <0.001). Within the HIV-infected group, children with HIV encephalopathy (n = 14) had poor white matter integrity when compared to ART-treated children without encephalopathy (n = 41), and there was significant myelin loss in ART-naive children (n = 20), compared with ART-treated children. ART-treated children had significant axonal damage in the corpus callosum (P = 0.009). Conclusion: Children infected with HIV, irrespective of treatment status, displayed significantly poorer white matter integrity and impaired cognition compared to HIV-negative controls. Our findings suggest that despite immune recovery in children on ART, they remain at risk for developing central nervous system disease, and that initiation of ART as early as possible may reduce the risk of developing white matter damage in ART-naive slow progressors.